The influence of hepatocyte growth factor on the proliferation and differentiation of stem cells - Rafał Bieś; Agnieszka Mikosińska; Jakub Parys; Mateusz Litwin; Patrycja Kałuziak; Marta Jajczak; Maciej Mossakowski; Aleksandra Witek; Martyna Kaźmierczak; Stanisław Jesionek (Journal of Education, Health and Sport)
Background: The HGF/c-Met signaling pathway is central to various biological processes, including tissue regeneration, cell proliferation, and differentiation. Dysregulation of this pathway has been implicated in cancer progression and poor prognosis. Despite its potential as a therapeutic target, the complexity of HGF/c-Met signaling and the associated challenges, such as off-target effects and limited understanding of its role in different disease contexts, pose significant obstacles to clinical translation.